Optimization of computer numerical control set-up parameters to manufacture rapid prototypes - Relvas, C.
This paper describes the study performed to determine the influence and optimize computer numerical control (CNC) set-up parameters to manufacture rapid prototype parts. The competitiveness of CNC was assessed relative to conventional rapid prototyping techniques by comparing dimensional precision, quality of the prototype, execution times and costs. CNC machine set-up parameters were first optimized using specimens of part of a hand dorsum model. Based on these findings, a CNC hand model was manufactured and compared with others manufactured by laminated object manufacturing (LOM), selective layer sintering (SLS) and stereolithography (SLA) rapid prototyping (RP) techniques. Overall, the study evidenced that CNC milling can be more or as competitive as the RP techniques tested. In fact, the CNC prototype was manufactured in significantly less time, was less expensive and presented excellent quality of dimensional control and surface texture. However, the quality of the CNC prototype is subject to expertise of the computer aided design/manufacture (CAD/CAM) operator.